White Blood Cell Changes Following Treatment with a Combination of Recombinant Human Granulocyte Colony Stimulating Factor (rhG-CSF) and Intravenous Immunoglobulin (IVIG) in Necrotizing Enterocolitis (NEC) - Kocherlakota, Prabhakar; Narayana, Sri K. P.; Blau, Jonathan; La Gamma, Edmund F. (Journal of Pediatric Infectious Diseases, 2017)
Objective We sought to determine whether recombinant human granulocyte colony stimulating factor (rhG-CSF) and intravenous immunoglobulin (IVIG) combination can increase white blood cell (WBC) count and improve the survival of extremely low-birth-weight (ELBW) neonates having necrotizing enterocolitis (NEC) with Bell stage II or above.Methods This retrospective chart review consisted of ELBW neonates with NEC provided with standard of care (standard group) or standard of care and a combination of rhG-CSF along with IVIG (treated group) at the discretion of the treating physician. Serial blood counts (days 0,1,2,3, and 7 to 10), survival, need for surgical intervention, time to reach full feeds, and time to discharge were compared between the two groups.Results The treated (27 neonates) and the standard (35 neonates) groups had birth weights of 857 ± 52 g and 1,009 ± 50 g; gestational ages of 26 ± 0.5 and 28 ± 0.5 weeks; WBC counts of 7,950 ± 6,452 and 14,105 ± 9,578/mm3; absolute neutrophil count (ANC) of 3,930 ± 5,152 and 7,117 ± 7,545/mm3, respectively (p < 0.05). During the study, WBC count and ANC increased in the treated group till days 7 to 10, but decreased till day 3 in the standard group (p < 0.05). ANC (11-fold) and monocytes (4-fold) increased in the treated patients with neutropenia by days 7 to 10 (p < 0.05). There was no change in the survival, need for surgery, time to reach full feed, or time to discharge between the two groups.Conclusion The combination of rhG-CSF and IVIG increased WBC, ANC, and monocytes in the treated group but did not affect the survival, need for surgery, time to reach full feed, or time to discharge.
Keywords: absolute neutrophil count; intravenous immunoglobulin; neutropenia; necrotizing enterocolitis; recombinant human granulocyte colony stimulating factor